Glyphosate hormesis induced by treatment via seed stimulates the growth and biomass accumulation in soybean seedlings - Krenchinski, Fábio Henrique [UNESP]; Costa, Renato Nunes [UNESP]; Pereira, Vinicius Gabriel Canepelle [UNESP]; Bevilaqua, Natália Cunha [UNESP]; Alcántara-de la Cruz, Ricardo [UNESP]; Velini, Edivaldo D. [UNESP]; Carbonari, Caio A. [UNESP] (Elsevier, 2024)
Glyphosate hormesis, identified as a potential means to enhance crop yields, encounters practical constraints because it is typically assessed through foliar applications. The expression and extend of hormesis in this approach are influenced by unpredictable environmental conditions, highlighting the need to explore alternative glyphosate application methods, such as seed treatment. This study aimed to assess glyphosate hormesis on growth rates and biomass accumulation in seedlings soybean cultivars. Two dose-response experiments [doses from 0 to 2880 g acid equivalent (ae) ha−1], one via foliar and one via seed, were conducted on three soybean cultivars [one non-glyphosate-resistant (NGR) and two glyphosate-resistant (GR, one RR and one RR2)]. In a subsequent experiment, three safe glyphosate doses (0, 90 and 180 g ae ha−1) applied via seed were evaluated on four soybean cultivars (two RR and two RR2). For foliar applications, the range of glyphosate doses increasing growth rates and dry biomass by 12–28 % were 5.6–45 g ae ha−1 for the NGR cultivar, of 45–720 g ae ha−1 for RR and of 11.25–180 g ae ha−1 for RR2. In the seed treatment, biomass increases of 16–60 % occurred at 45–180 g ae ha−1 for the NGR and RR cultivars, and 90–360 g ae ha−1 for RR2. Glyphosate doses of 90 and 180 g ae ha−1, applied via seeds, provided greater growth and biomass accumulation for the RR and RR2 soybean cultivars. Both foliar and seed applications of glyphosate increased growth and biomass accumulation in soybean cultivars, with seed treatments showing greater and more consistent enhancements. These findings propose practical and viable alternative for harnessing glyphosate hormesis to facilitate the early development of soybeans and potentially enhance crop yield.
Keywords: Absolute growth rate; Genetically modified crops; Glycine max (L.) Merrill; Glyphosate resistance; Plant height; Relative growth rate